2020
DOI: 10.3390/ijms21249597
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Orally Supplemented Melatonin on Larval Performance and Skeletal Deformities in Farmed Gilthead Seabream (Sparus aurata)

Abstract: The gilthead seabream larval rearing in continuous light is common in most Mediterranean hatcheries to stimulate larval length growth and increase food consumption. Several studies have shown that continuous light affects larval development and increases the prevalence of skeletal deformities. Melatonin is a crucial pineal neurohormone that displays daily secretion patterns, stimulates cell proliferation and embryonic development in Atlantic salmon and zebrafish, and improves osseointegration in mice and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Similarly, LL caused a higher lower jaw malformation in European sea bass ( Dicentrarchus labrax ) [ 67 ]. In gilthead seabream ( Sparus aurata ), Mhalhel et al (2020) [ 68 ] found that exogenous melatonin supplementation affected normal skeletogenesis and caused bone deformities by regulating the expression of genes related to bone formation. Fish receive external light signals and convert environmental time cues into endogenous biological signals through melatonin secretion [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, LL caused a higher lower jaw malformation in European sea bass ( Dicentrarchus labrax ) [ 67 ]. In gilthead seabream ( Sparus aurata ), Mhalhel et al (2020) [ 68 ] found that exogenous melatonin supplementation affected normal skeletogenesis and caused bone deformities by regulating the expression of genes related to bone formation. Fish receive external light signals and convert environmental time cues into endogenous biological signals through melatonin secretion [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fish receive external light signals and convert environmental time cues into endogenous biological signals through melatonin secretion [ 53 ]. Therefore, the increased bone deformity caused by LL may be related to the loss of coordination between the skeletal muscle and bone function caused by the disturbance of the circadian clock [ 68 ]. Although no bone deformities were observed in juvenile rainbow trout in the LL group, the significantly low whole-body ash and higher lipid deposition may be a warning sign of concern in the metabolic disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key points of those claims is the common belief that melatonin has no toxicity. A feature largely controverted for at least 30 years 17 and for which continuous interrogations are published, 18–31 most of which were consistently ignored or disregarded. Even more preoccupying, sentence such as “ Therefore, in view of the lack of toxicity of melatonin, the administration of pharmacological doses of this compound may significantly improve its efficiency as an antioxidant agent .” 32 Incidentally, some have shown that such antioxidant capacity of melatonin does not correspond to the experimental evaluation, for example, of the total antioxidant activity of blood 33 .…”
Section: Introductionmentioning
confidence: 99%
“…16 One of the key points of those claims is the common belief that melatonin has no toxicity. A feature largely controverted for at least 30 years 17 and for which continuous interrogations are published, [18][19][20][21][22][23][24][25][26][27][28][29][30][31] most of which were consistently ignored or disregarded. Even more preoccupying, sentence such as "Therefore, in view of the lack of toxicity of melatonin, the administration of pharmacological doses of this compound may significantly improve its efficiency as an antioxidant agent."…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative evidence has discussed that melatonin has a wide range of protective effects on various diseases, such as arrhythmia [ 13 ], primary biliary cholangitis [ 14 ], diabesity [ 15 ], non-small cell lung cancer [ 16 ], anovulatory disorders [ 17 ], cutaneous diseases [ 18 ], neurodegenerative diseases [ 19 , 20 ], and autism [ 21 ]. Furthermore, the beneficial effects of melatonin have also been studied in Sparus aurata [ 22 ] and Plasmodium falciparum [ 23 ]. In these studies, melatonin acted as a protector by regulating pathophysiological mechanisms and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%